Fatal hemothorax due to homicidal blunt trauma to carotid artery in the neck. (July 2014) - Behera, C; Krishna, Karthik; Singh, SR; Lalwani, Sanjeev
A 30-year-old man was found dead in a pool of blood inside his office room in the morning. Autopsy revealed a small contusion at the lower anterior part of neck, laceration on the left common carotid artery, hemothorax and a laceration over the nose with underlying fracture. On investigation, it was found that on the previous night the victim had been assaulted by his domestic help with an iron rod over head and neck. The blunt trauma to the neck resulted in laceration on the left common carotid artery and subsequently bled, causing fatal hemothorax. The authors report this case owing to the rarity of such patterns of injury leading to fatal outcomes, which may be overlooked due to the simple nature of external injuries.